“Preserve our culture”: The use of digital music platform in the ethnic music community - Yulinda Nur Fitriana; Riza Darma Putra (Universitas Bunda Mulia, 2022)
The use of digital music platforms can become effective media in ethnic music especially Betawi music, Pop music , RnB and Jazz genre. This digital music Platform can be used to preserve Indonesian ethnic songs. The purpose of this research is to find out the motives for the preservation of Betawi Music in the utilization of digital music platforms in Gambang Kromong Community. The study of the theory used uses and gratification and new media. In addition, the study of concepts used derivatives of the uses and gratification, digital music platforms used and the distribution of Music. This research is different from previous research existing to utilize digital music platform as an effective medium to preserve ethnic music, previous research utilizing digital music platform for promotional media. This research methodology uses a post-positivism paradigm with a qualitative approach and the type of this descriptive research, the analytical unit used by the organization, the research data collection techniques through interviews and documentation studies. This research Instrument researchers themselves, the data analysis techniques in the study of data collection, data reduction, data presentation and withdrawal of conclusions. Furthermore, validity of data used by the source of the sources by interviewing 5 informant. Based on the results of the study found that the utilization of digital music platform that is found by the work of Setia Muda foundations managed by Gema Nada Pertiwi tself become effective and preserve Betawi music in a digital way without using CDS and tapes to maintain its existence in the Betawi Music Foundation with a touch of Gambang Kromong on digital music platform. Keywords: Betawi music, Community media, Digital music platform, and Gambang Kromong.